Patient-centered medical homes and vision care for children: a cross-sectional analysis with data from the national survey of children's health 2018-2019 - Afua O. Asare; Brian C. Stagg; Carole Stipelman; Olivia J. Killeen; Patrice M. Hicks; Olaoluwa Omotowa; E. Eugenie Hartmann; Heather T. Keenan; J. D. Smith (BMC, 2024)
Abstract Background Vision screening as part of well-child visits is recommended annually for US children 3 to 6 years. However, 63% of children do not get a vision screening in well-child visits. The Patient-Centered Medical Home (PCMH) improves the receipt of preventive care visits in other medical specialties but it is unknown if it improves receipt of vision screening. The objective of this study is to determine whether caregiver-reported receipt of care in a PCMH is associated with receiving a vision screening test in a well-child visit for children 3 to 6 years in a pediatrician/general doctor's office ('primary care'). Method Population-based data for US children aged 3 to 6 years was derived from the National Survey of Children's Health (2018-2019). Children were excluded if they did not have a well-child visit in the previous 12 months. The primary exposure was receipt of care in a PCMH ('PCMH care'), and the primary outcome was receipt of a vision screening in primary care. Adjusted odds ratios (aOR) and predicted probabilities were computed for children with and without PCMH care. Results Among 9,587 children with well-child visits, 4,984 (50.9%) were males. There were 1,107 (23.3%) Hispanic, 6704 (52.8%) White/Non-Hispanic and 545 (11.8%) Black/Non-Hispanic children. There were 5,482 (51.8%) children who received PCMH care. Of those with PCMH care, 2,629 (52.2%) received a vision screening in primary care. Those with PCMH care (52.2%) had a higher odds of receiving a vision screening (aOR, 1.31; 95% CI 1.11, 1.55) in primary care compared to children without PCMH care (42.8%). The predicted probability of vision screening in primary care was 50.8% (95% CI 48.2, 53.5) for children that received PCMH care, and 44.3% (95% CI 41.3, 47.3) without PCMH care. Conclusions Caregiver-reported receipt of PCMH care was associated with a greater likelihood of vision screening for children 3 to 6 years in a well-child visit. Further studies are needed to understand the mechanisms through which PCMH care contributes to the greater odds of vision screening in primary care to inform the creation of strategic interventions to prevent vision loss and its long-term implications.